Tensile and interfacial properties of polyacrylonitrile-based carbon fiber after different cryogenic treated condition. (15th August 2016) - Zhang, Yinnan; Xu, Fujun; Zhang, Chuyang; Wang, Junjie; Jia, Zhemin; Hui, David; Qiu, Yiping
Abstract: Polyacrylonitrile-based carbon fibers are cryogenically conditioned both through a low cooling rate and a quench rate to explore the effects of cryogenic treatments on properties and micro-structures of carbon fibers. The internal structure, tensile properties and surface morphologies of the fiber are investigated. Increase in crystallinity and tighter packing of molecules of the fiber after the cryogenic treatments are observed regardless the cooling rate. After slow cooling cryogenic treatment, the inter-planar distance increases in the fiber axial direction and decreases in the fiber radial direction, resulting in 3% shrinkage of fiber diameter and extension in fiber axial direction. Scanning electron microscopy and atomic force microscopy analysis show slightly wider and deeper rill-like folds and 41% roughness increase for the fiber surfaces, leading to an increase in interfacial shear strength between the fiber and epoxy by 30.2%. In contrast, after sharp cooling cryogenic treatment, no obvious change is detected in inter-planar distance, fiber diameter, surface morphology and interfacial shear strength with epoxy. The bimodal additive Weibull distributions of tensile strengths for the cryogenic treated fibers show an increase of the bimodality parameter α and a decrease in scale parameter σ indicating higher probability of extrinsic defects but no significant mechanical degradation of the fiber after cryogenic treatments.